(3fNH GdCacGQ aj JfbjM eYGfj GdCNHGQs - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s; (3CMeO Hf eMeO Hf SdGeI Hf SdeI GdCROqj GdWMGhj, CHh LYaQ,J (B321 (3g` s ((3YeQ Hf YHO Gddg eMeO GdefXQGhi s)
(3ChdgG (B:s
(3HGH GdcdGe aj GdUdGI deG jMOK ajgG ef GdSgh s
(3BNQgG (B:s
(3HGH Uhe jhe GdTc s
(3HChdg dhMI ePgHI HQSe eMeO Hf EjfGd GdYdGFi hHLGfHgG JhbjYgs
(3fSNI GNQis
(3hbO cJHgG GdfGSN HQSe GdebQ GdCTQa eMeO Hf EjfGd GdYdGFis
(3fbdJ Yf GdeDda s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdMOjK h GdeUWdMs